Therapeutic effects of cyclophosphamide, dsDNA preparations and combinations thereof against Krebs-2 ascites cancer cells and various cancer transplants - E. A. Potter; E. V. Dolgova; A. M. Minkevich; Ya. R. Efremov; O. S. Taranov; V. V. Omigov; V. P. Nikolin; N. A. Popova; A. S. Proskurina; E. I. Vereschagin; A. V. Kozel; V. A. Rogachev; et al. (Вавиловский журнал генетики и селекции)
Existence of a small subset of cancer cells referred to as tumor initiating stem cells (TISCs) largely responsible for tumor progression and resistance to chemotherapeutic cytostatic drugs reperesent an important recent paradigm shift. The present work is the first report in the series of papers from our group where we describe the development of anticancer therapy based on the selective targeting of TISCs. Here were characterize a cytoreductive activity of cyclophosphamide (CP), double-stranded DNA (dsDNA) and combinations thereof against the TISC population present in mouse Krebs-2 ascites. We evaluated engraftment potential of Krebs-2 cancer cells treated in ascites-bearing mice in vivo, followed by re-engraftment to congenic recipient mice in a form of a solid graft. These data indicate that with our approach TISCs can be completely eliminated even from a well-established ascites. We demonstrate that dsDNA-internalizing and CD34-positive cells are more sensitive to the synergistic effects of CP and dsDNA. When Krebs-2 ascites are treated with human DNA 1-12 hours post CP injection, this results in either elimination of cells that internalize TAMRA-labeled DNA (TISCs) or alters their phenotype, which is accompanied with the loss of surface expression of CD34. Next, we show that the timepoint 18 hrs post CP treatment is critical to the ongoing repair process in that it divides the repair into two phases: nucleotide excision repair + dsDNA break repair and homologous recombination. Importantly, both of these phases can be conveniently used for targeting the tumorigenic potential of the graft. In the context of monotherapy, CP is most effective against ascites grafts when administered as serial injections. To achieve maximum efficiency, the timing of consecutive injections must match the time when cancer cells found at G2/M during the first injection enter G1/S and/or the time of active repair via homologous recombination.